Women and the Modelling of Victorian Sculptural Discourse. (3rd April 2017) - Fraser, Hilary
Abstract : This article focuses on a selection of nineteenth-century female art critics and connoisseurs who were prominent art writers of their day but whose contribution to the critical history of sculpture has since fallen out of view. I argue that women modelled a sculptural discourse that was distinctive, often personally driven and biographically inflected, and gendered. They deployed various forms of life writing – biography, autobiography, memoir, personal reminiscence, Bildungsroman, letters, gallery journals – as a vehicle for connoisseurship about sculpture. Cosmopolitan in outlook, they understood the importance of personal networks in both the production and the reception of art. Furthermore, female writers responded to the corporeal connections between viewers, models and figurative sculpture in their work. Writing about the three-dimensional representation of the human body in sculptural form enabled women to comment obliquely on issues such as female creativity, sexuality and education.